MODEL PEMBELAJARAN BERBASIS MASALAH, PENGGUNAAN MEDIA AUDIO VISUAL, DAN VARIASI MENGAJAR GURU TERHADAP HASIL BELAJAR IPS TERPADU - Sebastian Galileo; Lilik Sri Hariani; Naim Naim (Jurnal Riset Pendidikan Ekonomi, 2019)
This study aims to determine how much influence these three factors partially and simultaneously on student learning outcomes. This research was conducted at the junior high school of Pakisaji noble mind. The research population was all VIII grade students, totaling 131 students. This sample of study included 67 students, the sampling method was random sampling. Based on the results of the F test it was found that there was a significant simultaneous effect between the independent variables (problem based learning models, the use of audi visual media and variations of teacher teaching) to the dependent variable (learning outcomes). The results of this t-test show that the use of problem-based learning models on learning outcomes has a significant effect, the use of audio-visual learning media on learning outcomes has a significant effect, and variations in teacher teaching on learning outcomes have a significant effect. Based on the results of this research it is expected that in an effort to improve student learning outcomes, teachers should be able to apply the right model in KBM, use learning media according to students' needs, and apply the variety of teaching when delivering learning material.